2015
DOI: 10.3389/fmicb.2015.00636
|View full text |Cite
|
Sign up to set email alerts
|

The spatial biology of transcription and translation in rapidly growing Escherichia coli

Abstract: Single-molecule fluorescence provides high resolution spatial distributions of ribosomes and RNA polymerase (RNAP) in live, rapidly growing Escherichia coli. Ribosomes are more strongly segregated from the nucleoids (chromosomal DNA) than previous widefield fluorescence studies suggested. While most transcription may be co-translational, the evidence indicates that most translation occurs on free mRNA copies that have diffused from the nucleoids to a ribosome-rich region. Analysis of time-resolved images of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
123
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(147 citation statements)
references
References 66 publications
15
123
4
Order By: Relevance
“…Similar electron cryotomography analysis of the cellular ultrastructure of logarithmically growing cultures of C. jejuni revealed ribosome exclusion zones at cell poles (80). Also consistent with extra-nucleoid distribution of ribosomes, 5S rRNA was detected as an array of fluorescent particles distributed along the cell or the cell poles in E. coli (33), indicating specific localization of ribosomes outside the nucleoid in E. coli, which is in agreement with enrichment of ribosomal proteins at the cell periphery and cell poles in both E. coli (84) and B. subtilis (82, 85). While several ribosomal proteins (L1, S2, L7/L12) are enriched at either of the cell poles and the translation factor EF-Tu colocalizes with the bacterial cytoskeleton protein MreB, it remains unclear how many of these localized translation factors are incorporated into actively translated ribosomes (reviewed in (86)).…”
Section: Localized Mrna Translation and Degradationsupporting
confidence: 72%
See 1 more Smart Citation
“…Similar electron cryotomography analysis of the cellular ultrastructure of logarithmically growing cultures of C. jejuni revealed ribosome exclusion zones at cell poles (80). Also consistent with extra-nucleoid distribution of ribosomes, 5S rRNA was detected as an array of fluorescent particles distributed along the cell or the cell poles in E. coli (33), indicating specific localization of ribosomes outside the nucleoid in E. coli, which is in agreement with enrichment of ribosomal proteins at the cell periphery and cell poles in both E. coli (84) and B. subtilis (82, 85). While several ribosomal proteins (L1, S2, L7/L12) are enriched at either of the cell poles and the translation factor EF-Tu colocalizes with the bacterial cytoskeleton protein MreB, it remains unclear how many of these localized translation factors are incorporated into actively translated ribosomes (reviewed in (86)).…”
Section: Localized Mrna Translation and Degradationsupporting
confidence: 72%
“…For example, inner-membrane bound ribosomes in E. coli that are actively engaged in translation (89) might play a role in specific translation of inner membrane proteins. In C. crescentus and another alpha-proteobacterium Sinorhizobium meliloti , ribosomes are detected throughout the cell including the nucleoid region (64, 90), which is different from the ribosome/nucleoid segregation observed in E. coli and B. subtilis (82, 84) . Hereby, it was suggested that, mRNA-bound ribosomal subunits show limited mobility in C. crescentus due to the observed limited dispersion of their mRNA targets from their site of transcription (64, 90, 91).…”
Section: Localized Mrna Translation and Degradationmentioning
confidence: 76%
“…10 Fluorescently labeled ribosomal proteins S2 and L1, proxies for ribosomes in E. coli and B. subtilis, respectively, were found enriched at the cell poles, spatially excluded from the nucleoid on the hundreds of nanometer scale. 11,12 Similar fluorescence imaging studies in Caulobacter revealed no apparent separation of ribosomes and the nucleoid, though did suggest that ribosome diffusion throughout the cell was spatially confined. 10 However, because the Caulobacter cell is only ~500 nm by ~3.5 μm in size, the diffraction-limited resolution of conventional fluorescence microscopy would obscure any organization or motion of the components of the degradosome or the ribosome that are on length scales of less than ~200 nm.…”
mentioning
confidence: 84%
“…Note that the nucleoid here has finer resolution (one bead per nucleotide) than the nucleoid model in a or d. c Model of facilitated diffusion, where the DNA is shown in green and orange (binding site), the DNA binding protein (DBP) in red and the crowders in blue and gray. d Model of nucleoid compaction: states of the nucleoid (red particles, top and bottom) in the presence of ribosomes and polyribosomes (green particles, top) and 30S and 50S ribosomal subunits (blue and yellow particles, bottom) (Bakshi et al 2015). e Nuclear body particle (red) assembly under the influences of a weak inter-molecular attraction and crowding agents (blue) at increasing volume fraction ϕ (Cho and Kim 2012b) Fig.…”
Section: Computational Models Of Diffusion In the Cytoplasmmentioning
confidence: 99%
“…The testing for a possibly more expanded state of the genetic material, compatible with the co-transcriptional translation, was explored by Bakshi et al (2015), who refined the model in Mondal et al (2011) by allowing for the reversible disassembly of 70S ribosomes into the 30S and 50S subunits. Indeed, the authors observed that the ribosomal subunits were able to penetrate into the nucleoid and expand it (Fig.…”
Section: Computational Models Of the Genetic Materialsmentioning
confidence: 99%